Aggregation Phenomena in Photobicyclised Pyridinium Salts - Encina-Rojas, M; Caroli-Rezende, M; Negrete-Vergara, C; Negrete-Vergara, C (Royal Society of Chemistry, 2017)
The possible formation of aggregates in a solution of two planar heterocyclic salts, 2-phenylbenzo[8,9]quinolizino[4,5,6,7-fed]phenanthridinylium tetrafluoroborate (PQPBF4) and thienyl-substituted 2-phenylbenzo[ij]pyrido[2,1,6-de]dithieno[3,2-b:2′,3′-g]quinolizin-13-ium perchlorate (BPDTQClO4), was investigated in organic solvents and in water, by the analysis of their UV-Vis and fluorescence spectra. The results provided evidence for the formation of H-aggregates in water, a conclusion supported by theoretical calculations of the transition energies of the cationic monomers (PQP+ and BPDTQ+) and of the dicationic π-stacked H-dimers in water. © 2017 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.